Getting ahead through advanced vocational training : German background report on the OECD study "Skills beyond school" - Hippach-Schneider, Ute [Verfasser]; Hanf, Georg [Verfasser]; Müller, Normann [Verfasser]; Schandock, Manuel [Verfasser]; Schneider, Verena [Verfasser] (My University, 2012)
"This OECD-endeavour started in 2011 and deals predominantly with postsecondary skills acquired after initial training. This phase of training - advanced vocational training, continuing training - is continuously gaining importance in view of enterprises being forced to be more and more competitive in dynamic economies. These enterprises are all the more in need of highly skilled workers. This was the starting point for OECD to prepare an international comparative overview on participating countries as well as specific reviews dealing with countries under this activity. Under the auspices of the Federal Ministry of Education and Research (BMBF) and the Standing Conference of the Länder Minsters of Education the focus of the national report was laid on formal advanced training programs, the respective qualifications at level 5 B on the scale of the International Classification of Education (ISCED). They include advanced training courses according to the Vocational Training Act (BBiG) and the Crafts Regulation Code (HwO). Additionally courses at trade and technical schools (Fachschulen) and specialized academies were examined. As they are not regarded as part of the higher education sector, courses at universities of cooperative education (Berufsakademien) or cooperative state universities (Duale Hochschulen) are not part of the report. Likewise, schools for the health sector and for public administration are excluded because they mainly deal with initial vocational education and training. All the participating countries had to conceive their own national background reports with the OECD only furnishing guidelines for the structure of the respective reports and the questions to be answered. That was also the basis for the "National Background Report". State regulated formal vocational training with a strong involvement of company practitioners is at the core of a wide range of advanced training programs in Germany. The "National Background Report for Germany" not only deals with responsibilities and structure, but also with aspects of participation and continuing education counseling. It illustrates among others possibilities of transfer to higher education, i.e. the aspect of permeability. Due to the restricted thematic focus a comprehensive overview of all advanced training opportunities was neither possible nor intended." (BIBB-Doku)
Keywords: S 1.5.2 Berufliche Weiterbildung; S 3.3 Bildungsträger; L 7 Prüfungen; Fortbildung; Anpassungsfortbildung; Aufstiegsfortbildung; Bildungsträger; Finanzierung; Fortbildungsordnung; Fortbildungsprüfung; Berufsbildungsgesetz; Handwerksordnung; Fachschule